Common alpha globin genes (HBA1 and HBA2) mutations in Filipino patients with alpha thalassemia - Silao, Catherine Lynn T.; Fabella, Terence Diane F.; Naranjo, Maria Liza T.; Barnuevo, Mayceemae M.; Padilla, Carmencita D.; Yuson, Ernesto dJ. (2021)
"Alpha (a) thalassemia results from the absence/reduced synthesis of the a-globin subunit of hemoglobin (Hb). Mutational variants in the HBA1 and HBA2, which code for a-globin, have been reported to cause varying degrees of disease severity. These variants are unique for every population. However, local data on a-globin gene mutations in Filipino a-thalassemics is currently lacking. This study aimed to identify common a-globin gene mutations in Filipino patients. suspected with a-thalassemia"-title page.
Includes bibliographical references.
Keywords: Blood -- Analysis; Gene expression; Filipinos; Hemoglobinopathy